2020
DOI: 10.5812/jjm.106825
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Antifungal Susceptibility of Candida Species Isolated From Vulvovaginitis in Jahrom City, South of Iran

Abstract: Background: Vulvovaginal candidiasis (VVC) is a significant health issue due to Candida spp. Although Candida albicans is considered a major causative agent of vaginal candidiasis, non-albicans species have increased during previous decades. Objectives: This research aimed at molecular identification and assessing antifungal susceptibility of VVC isolated Candida spp. Methods: A professional physician examined two hundred and ninety-five suspected females with vaginitis. The specimens were collected by sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(36 reference statements)
4
3
0
Order By: Relevance
“…The availability of epidemiological data from around the world showed that the prevalence rate of VVC among reproductive age women had many differences [5,32,35]. The results of our study were similar to that of previous researches in Turkey (49.2%) [38], Egypt (50.4%) [21], Iran (50.5 and 51.6%) [39,40]. Lower yeast prevalence was reported from Greece (12,1%) [41], UAE (13.88%) [42], India (20.0%) [43], Gabon (28.52%) [44], Ghana (36.5%) [45], Lebanon (39.0 and 44.8%) [1,33], and Tanzania (45.7%) [46].…”
Section: Discussionsupporting
confidence: 88%
“…The availability of epidemiological data from around the world showed that the prevalence rate of VVC among reproductive age women had many differences [5,32,35]. The results of our study were similar to that of previous researches in Turkey (49.2%) [38], Egypt (50.4%) [21], Iran (50.5 and 51.6%) [39,40]. Lower yeast prevalence was reported from Greece (12,1%) [41], UAE (13.88%) [42], India (20.0%) [43], Gabon (28.52%) [44], Ghana (36.5%) [45], Lebanon (39.0 and 44.8%) [1,33], and Tanzania (45.7%) [46].…”
Section: Discussionsupporting
confidence: 88%
“…Similar reports have been reported in previous studies [18][19][20]. The data in different parts of the world have recorded higher rates of C. albicans [21][22][23][24], while lower rates were also reported [25][26][27][28].…”
Section: Discussionsupporting
confidence: 89%
“…Several previous studies were reported that C. albicans (76 -89%) was the most common causative agent of infection in women with VVC, followed by C. glabrata (7 -16%) from different countries (1,2,(11)(12)(13)(14)(15). The rise of VVC incidence and drug resistance leads to an important public health issue and challenges clinician's treatment strategies (1).…”
Section: Discussionmentioning
confidence: 99%